Dinamika Populasi dan Struktur Komunitas Serangga Parasitoid Pada Berbagai Fase Pertumbuhan Padi Sawah Di Gampong Gintong, Kecamatan Grong-Grong, Kabupaten Pidie - Nanda Fatmala; Aidil Amar; Diah Fridayati; Tengku Dhean; Sayed Ahmad Zaki Yamani (Jurnal Penelitian Pertanian Terapan, 2026)
Parasitoid insects play a crucial role in the wetland rice ecosystem as natural enemies of key pests. This study aimed to assess the population dynamics and community structure of parasitoid insects across four rice growth phases in Gampong Gintong, Grong-Grong District, Pidie Regency. Sampling was conducted at 25 observation units (5 transects × 5 points) using yellow sticky traps, sweep nets, and aspirators at 14, 28, 49, and 70 Days After Transplanting (DAT) with three replications. A total of 28 individuals from six parasitoid families of two orders were recorded: Braconidae, Ichneumonidae, Chalcididae, and Eulophidae (Hymenoptera), and Pipunculidae and Tachinidae (Diptera). Population density was highest at the Late Vegetative phase (28 DAT) at 3.00 individuals/plot and lowest at the Grain-Filling phase (70 DAT) at 1.67 individuals/plot. One-way ANOVA showed no significant overall difference among phases (F = 3.556; p = 0.067), although Tukey HSD identified a significant difference between the Late Vegetative and Grain-Filling phases. Shannon-Wiener index (H’) ranged from 0.673 to 1.277, Pielou’s evenness (E) from 0.870 to 0.971, and Simpson’s dominance (C) from 0.190 to 0.400. Air temperature increased from 27.9°C at the Late Vegetative phase to 30.1°C at Grain-Filling, showing a strong negative correlation with parasitoid abundance (r = −0.98; p = 0.021), while relative humidity showed a strong positive correlation (r = +0.96; p = 0.038). Braconidae (42.86%) and Ichneumonidae (39.29%) were present across all growth phases and showed potential as biological control agents in integrated pest management programs in Pidie Regency.